2012
DOI: 10.1007/s00535-012-0701-1
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic determinants of hepatitis E virus and vaccine-induced immunogenicity and efficacy

Abstract: There is emerging evidence for an under-recognized hepatitis E virus (HEV) as a human pathogen. Among different reasons for this neglect are the unsatisfactory performance and under-utilization of commercial HEV diagnostic kits; for instance, the number of anti-HEV IgM kits marketed in China is about one-fifth of that of hepatitis A kits. Over the last two decades, substantial progress has been achieved in furthering our knowledge on the HEV-specific immune responses, antigenic features of HEV virions, and dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 71 publications
1
26
0
Order By: Relevance
“…Initial sandwich phage ELISA screening results (Table 1) were confirmed by a competitive inhibition assay that uses recombinant ORF2 protein as the antigen to compete with phagotopes for anti-HEV reference serum binding [24]. Six mimotopes efficiently competed with HEV for binding to specific antibodies (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Initial sandwich phage ELISA screening results (Table 1) were confirmed by a competitive inhibition assay that uses recombinant ORF2 protein as the antigen to compete with phagotopes for anti-HEV reference serum binding [24]. Six mimotopes efficiently competed with HEV for binding to specific antibodies (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…In the case of HEV, most of the commercial and in-house serological assays are based on selected regions of immobilised ORF2 capsid protein, and some include ORF3 protein [24,25]. The strategies for HEV vaccine development has been concentrated in the expression of several truncated recombinant ORF2 capsid proteins as immunogens.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a recombinant VLP-based vaccine against Hepatitis E virus infection, Hecolin ® , was licensed and launched in China (Zhao et al 2013a) after demonstration of vaccine safety and efficacy with over 115,000 volunteers enrolled in a large-scale Phase III trial (Zhu et al 2010). The key antigenic determinants reside on the viral capsid comprised of a single protein encoded by ORF2.…”
Section: Hev Vlp Vaccinementioning
confidence: 98%
“…The product consistency of the HEV 239 8,20,23 vaccine was demonstrated using a combination of biophysical, biochemical and immunochemical methods. Results from these methods demonstrated that different vaccine batches have comparable antigen characteristics or CQAs.…”
Section: Structural Basis For the Hev 239 Vaccinementioning
confidence: 99%